More chills : 12 more chilling tales and exciting adventures : with exercises to help you learn - Goodman, Burton (Lincolnwood, Ill. : Jamestown Publishers, 1997)
Contains adaptations of twelve short stories of adventure and surprise by famous and lesser-known authors, each with exercises designed to help students develop reading and literature skills.
5.8
5-8
Keywords: Readers -- Juvenile literature; Readers; Reading materials